“WE ARE RESILIENT BY FORCE, NOT BY CHOICE”: TERRIFYING BOMBAY IN NEW BOLLYWOOD CINEMA (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
As the home of the Hindi film industry, Bombay has occupied center stage in Bollywood’s imaginary of the modern metropolis. Over the last decade, however, cinematic representations of Bombay have undergone drastic transformations: from being the terrain of gang warfare in the 80s and 90s, the cinematic city has become the primary target and habitat of global terrorism. Bollywood’s rendition of a city perpetually under siege resonates with the series of attacks that have plagued the hapless metropolis since 1993. I interrogate Bollywood’s shifting relationship with its hometown and its audiences via two landmark films—A Wednesday and Aamir (2008). I am especially interested in the dialectics of ordinariness and extraordinariness that inflect articulations of the city and its citizenry. In both films a ‘common’ individual is called upon to perform uncommon tasks in order to negotiate the space of potential devastation that is now Bombay. Spectacular performances of technologies and stylistic devices generate the cinematic city as an affective locus of dread. I pay special attention to cinematography and editing, which enable the filmic figuration of the city in these recent films.